Relapse prevention therapy for internet gaming disorder in Swedish child and adolescent psychiatric clinics: a randomized controlled trial - André, Frida; Kapetanovic, Sabina; Einarsson, Isak; Trebbin Harvard, Sunna; Franzén, Leonard; Möttus, Annika; Håkansson, Anders; Claesdotter-Knutsson, Emma (Frontiers in Psychiatry, 2023)
Objectives: To evaluate the effectiveness of relapse prevention (RP) as a treatment for internet gaming disorder (IGD).Design: Randomized controlled trial.Setting: Three child and adolescent psychiatry (CAP) units in Region Skåne, Sweden.Participants: Children aged 13-18 years, coming for their first visit to CAP during 2022, were screened for gaming behaviour. Those who met the proposed DSM-5 criteria for IGD were offered participation in the trial, if they had the capacity to provide written informed consent and if they spoke Swedish. A total of 111 CAP patients agreed to participate. Out of those, 11 patients were excluded due to incorrect inclusion such as young age (n = 1), or due to the absence of responses to follow-up measures (n = 9). After exclusion, 102 participants remained (intervention = 47, control = 55)The intervention, RP, is based on cognitive behavioural treatment (CBT) and was provided individually, comprising of five to seven 45-minute sessions over a period of five to seven weeks versus treatment as usual.Outcome measures: Participants were assessed with Game Addiction Scale for Adolescents pretreatment (GASA) (baseline), post-treatment (treatment group only), and three months after baseline (follow-up).The repeated measures ANOVA showed a significant interaction effect between treatment and time. Both the control group and treatment group lowered their mean GASA score from baseline to follow-up significantly, but the improvement was greater in the treatment group (mean difference in control group -5.1, p<0.001, 95% CI= -3.390 to -6.755, mean difference in treatment group -9.9, p<0.001, 95% CI= -11.746 to -8.105).Conclusions: RP was found to be superior to treatment as usual in terms of reduction of IGD symptoms. Future research should address which aspects within a given treatment are effective, who benefits from treatment, in what aspects, and why.